Assessment of the Ecological and Economic Sustainability of Russian Urban Agglomerations - Kaizer , Philipp Yu.; Brel , Olga A.; Zaytseva , Anna I.; Lisina , Natalia L. (Economy of Regions, 2025)
Urban agglomerations in the Russian Federation are receiving increasing attention due to their role in economic growth, particularly in light of the socio-economic imbalance between cities and peripheral regions. This study aims to assess the ecological and economic sustainability of urban agglomerations in Russia by using cluster analysis to identify groups of agglomerations with similar sustainability profiles. The research relies on statistical, comparative geographic, and cluster analysis methods. The study is based on data from the Federal State Statistics Service, environmental protection reports, and materials from the Institute for Economics of the City, which cover various economic, social, and environmental aspects. Through the analysis, four distinct clusters of urban agglomerations were identified, and the key factors contributing to their sustainability were determined. The study found that factors such as population density, gross emissions, total waste production, and waste intensity are the primary contributors to lower environmental sustainability. As a result, the agglomerations in the first cluster were identified as the least environmentally and economically stable. The agglomerations in the third and fourth clusters were slightly more stable, while those in the second cluster exhibited the highest levels of stability. These findings can serve as a foundation for developing strategies and practical solutions to enhance the ecological and economic sustainability of urban agglomerations in Russia. These findings can also be used for urban planning, forecasting development, creating environmental ratings, and implementing effective environmental protection measures at both the regional and national levels.